Pemanfaatan Media Relations PT Universal Karya Mandiri Dalam Meningkatkan Citra Perusahaan - Aisyiah Indah Permata; Sholihul Abidin; Renita Kurnia (Prosiding, 2023)
The purpose of this research is to find out how PT Universal Karya Mandiri utilizes its media relations to improve the company's image. In the digital era, media relations have evolved with the existence of social media, online platforms, and faster access to information. This research method is skinative with the research data source is secondary data sources. Data collection through observation and documentation, the results showed that several forms of media utilization carried out by PT Universal Karya Mandiri were press ghathering, press lunch and entertain, sponsorship, and annual events. So that PT Universal Karya Mandiri can improve the company's good image.